Factors associated to academic performance in university students from the socio-economic perspective: A study at the University of Costa Rica - Garbanzo Vargas, Guiselle María (2013)
Since the academic performance of higher education students is one of the most outstanding and far-reaching quality indicators of the academic activity, a quantitative research was conducted with a cohort of students from the University of Costa Rica, who were graduated or in the last years of their study program. A questionnaire was applied to these students in a personalized way. The study refers to the factors associated to academic performance from the socioeconomic perspective. The general objective was to analyze the factors associated to the academic performance of those students with the highest scholarship category because of their socio-economic situation, and students who did not request a scholarship because of the high/low demand of study programs at the University of Costa Rica. In this way, this research examines the problem of academic performance based on the socio-economic situation of students; this variable is very important for having an explanatory framework and providing input related to institutional policies in the area of public higher education. The study helped us to confirm that academic performance is a very complex multi-causal process that results from the interaction of multiple social, personal, academic-institutional factors, which may vary from one population to another. It also confirmed the existence of significant differences between linear variables: university satisfaction index, study habits index, index of university studies support, satisfaction rate about teachers, and socioeconomic situation; however, the study reported that there are no differences in the most important variables, including grade point average and admission score.